Use of the Section Technique Method to Obtain Reliability Index Through SAIDI and SAIFI Values PT PLN (Persero) Tarakan - Sartika, Linda; Prasetia, Abdul Muis; Hasdiah, Miftahulhuda Primananda (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2025)
With the increasing demand for electrical energy in the city of Tarakan must be accompanied by increasing the quality of distribution to customers to provide the flow of electrical energy in a fairly reliable power. in this study aims to meet and analyze the reliability of the power distribution system based on SAIFI and SAIDI by using the section technique method. Distribution system reliability is one of the ways to improve the quality of electrical energy services to consumers. Section technique by breaking the system into several parts and then analyzing each part so that the results can be optimal and the section is divided into 10 sections of 10 feeders in Tarakan city. There are several system reliability indices as a reference in analyzing the SAIFI and SAIDI. As for the calculation results of the section technique method, the SAIFI value analyzed is 2.393765 times / year, it can be seen that it meets the specified standards. While the SAIDI value of 1.760446 hours / year appears to meet the standard.